2005
DOI: 10.1158/1535-7163.mct-05-0244
|View full text |Cite
|
Sign up to set email alerts
|

Class III β-tubulin expression in tumor cells predicts response and outcome in patients with non–small cell lung cancer receiving paclitaxel

Abstract: Both fundamental and clinical studies suggest that class III B-tubulin expression is associated with resistance to taxanes and constitutes a prognostic factor in several solid tumors. In this study, we assessed the prognostic and predictive value of class III B-tubulin in tumors of patients with locally advanced or metastatic non -small cell lung cancer (NSCLC) treated with paclitaxel-based or other regimens that did not include tubulin-binding agents. Expression of class III B-tubulin was examined immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
168
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 206 publications
(177 citation statements)
references
References 28 publications
6
168
2
1
Order By: Relevance
“…The only other available study 39 on breast cancer patients treated with neoadjuvant docetaxel reported that Class III b tubulin mRNA increase was associated with a poorer probability of clinical response to docetaxel. Other clinical experiences concerning Class III b tubulin and response to taxanes were conducted in small series of patients with ovarian, 40 epithelial lung advanced cancers 41,42 or gastric cancer 43 confirming a relationship between of Class III b tubulin tumor expression and paclitaxel-resistance. These studies considering Class III b tubulin expression but also other potential biomarkers involved in mechanisms of paclitaxelresistance concluded that this b tubulin isoform could be 1 of the most relevant mechanism for clinical resistance to taxanes.…”
Section: Discussionmentioning
confidence: 81%
“…The only other available study 39 on breast cancer patients treated with neoadjuvant docetaxel reported that Class III b tubulin mRNA increase was associated with a poorer probability of clinical response to docetaxel. Other clinical experiences concerning Class III b tubulin and response to taxanes were conducted in small series of patients with ovarian, 40 epithelial lung advanced cancers 41,42 or gastric cancer 43 confirming a relationship between of Class III b tubulin tumor expression and paclitaxel-resistance. These studies considering Class III b tubulin expression but also other potential biomarkers involved in mechanisms of paclitaxelresistance concluded that this b tubulin isoform could be 1 of the most relevant mechanism for clinical resistance to taxanes.…”
Section: Discussionmentioning
confidence: 81%
“…More recently, acquired expression of class III b-tubulin was not seen in another study of ovarian cancer, however, the pre-treatment level of this isotype did act as an independent prognostic indicator of poor outcome [26]. Similarly, increased expression of classes I and III b-tubulin in breast [27] and class III b-tubulin non-small cell lung cancer [28] also appear to predict poor outcomes with Paclitaxel and Docetaxel, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…stathmin, tau), as well as enhanced 3-tubulin expression might be correlated with reduced response to antimicrotubule agentbased chemotherapy or worse outcome in a variety of tumor settings. In in vitro studies or in clinical investigations, enhanced expression of 3-tubulin has shown to play a crucial role in the development of chemoresistance to antimicrotubule agents in a variety of tumors such as lung, breast, prostate or orarian cancers (61)(62)(63)(64)(65)(66), and has be considered as a predictive marker of paclitaxel resistance (25,(67)(68)(69)(70). Nevertheless, the mechanism underlying 3-tubulin expression still remains unclear.…”
Section: Enhanced 3-tubulin Expression By E2/ermentioning
confidence: 99%